Seniors, iTV and content about Social Services: Clarifying the relationship - Carlos, Mariana (2018)
Over the years, television has been seen as a mean of enriching human development. The technological evolution of this mean of communication led broadcasters to deliver more attractive and diversified contents. Hence, traditional broadcasting evolved from the traditional passivity to the granting of a participatory role for viewers, creating a new paradigm – Interactive Television. Elderly viewers are great consumers of television and represent a considerable portion of people who can take advantage of the interactivity potentialities. Most of the times, changes in social services take too much time to reach elders due to their technological, sensory or cognitive limitations, which tend to occur with the aging process. In this framework, the research team aim to find principles for the development of content about social services considering iTV potential and the limitations of elderly viewers. For accomplish this goal the team developed audiovisual content and also evaluated its effectiveness.